2021
DOI: 10.1111/asj.13569
|View full text |Cite
|
Sign up to set email alerts
|

Feeding cashew nut shell liquid decreases methane production from feces by altering fecal bacterial and archaeal communities in Thai local ruminants

Abstract: The effect of feeding cashew nut shell liquid (CNSL) on fecal fermentation products and microbiota was investigated in Thai native cattle and swamp buffaloes. Four of each animal were fed rice straw and concentrate diet with control pellets without CNSL for 4 weeks, followed by the same diet with pellets containing CNSL for another 4 weeks, so that CNSL was administered at a level of 4 g/100 kg body weight. Feces were collected the last 2 days in each feeding period. CNSL alkyl phenols were recovered from fece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
2
8
0
Order By: Relevance
“…The findings of the present study suggest that CNSL addition is useful for decreasing methane emission from fresh feces that contains more fermentable materials than feces left for an extended period of time. The mitigation of methane emissions was associated with an alteration in SCFA production patterns, which, in turn, was affected by shifts in fecal microbes, as has been reported previously in a CNSL feeding study (Tamori et al, 2021). As another option, instead of adding CNSL in its refined form, cashew shells, preferably finely ground, could be directly applied to feces for this purpose.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The findings of the present study suggest that CNSL addition is useful for decreasing methane emission from fresh feces that contains more fermentable materials than feces left for an extended period of time. The mitigation of methane emissions was associated with an alteration in SCFA production patterns, which, in turn, was affected by shifts in fecal microbes, as has been reported previously in a CNSL feeding study (Tamori et al, 2021). As another option, instead of adding CNSL in its refined form, cashew shells, preferably finely ground, could be directly applied to feces for this purpose.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, an effective strategy for minimizing the amount of methane emissions from feces can be achieved by direct addition of CNSL at the early stage of fecal storage. Tamori et al (2021) reported that supplementing the diet of Thai native cattle and swamp buffaloes with CNSL altered fecal microbiota and lowered the methane production potential of the feces. They concluded that CNSL supplementation modifies not only rumen fermentation but also hindgut and fecal fermentation to suppress methane generation, which can contribute to mitigating the environmental burden associated with maintaining ruminant livestock, especially in regions where feces is often left untreated for extended periods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations